'Job opportunities for the youth': Competing and overlapping discourses on youth unemployment and work informality in Egypt. (May 2016) - Barsoum, Ghada
Employment informality, or employment without access to work contracts and social insurance, is the norm for Egypt's working youth, including educated youth. Despite the policy focus on youth as a demographic group, particularly after the country's recent political developments, informality and precariousness remain largely absent from the policy discourse in Egypt. Youth unemployment rates continue to be the main yardstick for youth welfare in the country. Drawing on Bacchi's 'What is the Problem Represented to be?' (WPR) approach, the analysis in this article seeks to elucidate the implicit assumptions in this policy approach. The article juxtaposes the policy discourse on youth unemployment and informality to that of interviewed educated youth working informally. The two discourses overlap in assigning the state a central role in providing jobs in the public service for youth and in marginalizing the potential to address issues of employment precariousness outside such jobs. They are in discord, however, when young people articulate strong feelings of injustice when these prized jobs are not made available.